The Impact of Mass Antigen Testing for COVID-19 on the Prevalence of the Disease - Martin Kahanec; Lukáš Lafférs; Bernhard Schmidpeter (Institute of Labor Economics (IZA), 2021)
More than 100 million people have been infected and 2.5 million people have died of COVID-19 globally as of February 2021. Mass antigen testing could help to mitigate the pandemic and allow the economy to re-open. We investigate the effects of mass antigen testing on the pandemic, using data from a uniquely designed nation-wide testing implemented in Slovakia in Autumn 2020. After the first round, only districts above an ex-ante unknown prevalence threshold were re-tested. Comparing districts above and below the threshold using a quasi-experimental design, we find that repeated mass antigen testing reduced infections by about 25-30% and decreased R0 by 0.3 two weeks after the re-testing; the effects on incidence peaked around that time and all effects gradually dissipated afterward. These results suggest that mass testing could be an effective tool in curbing the spread of COVID-19, but for lasting effects regular retesting would be necessary.
Keywords: D04; I18; J22; 330; COVID-19; COVID-19 policies; antigen testing; non-pharmaceutical interventions; mass testing